Comparison of Social Distancing Practices among Genders during Covid-19 Pandemic - Naila Parveen et al; Saima Athar; Lubna Riaz; Ikhlas Ahmed; Kainat Sattar Shaikh; Mahnoor Channa (ziauddin University, 2024)
Background: The rapid transmission of corona virus from symptomatic as well as non-symptomatic subjects has caused a serious health crisis globally. The Ministry of health, to curb this lethal pandemic, has imposed various standard operating procedures to minimize its spread. Amongst them, avoiding close contact with others limits the spread of Covid-19 and reduces the risk of infection. The study aimed to compare barriers and motivators of social distancing practices among undergraduate male and female students during Covid-19 pandemic. Methods: This cross-sectional study was conducted at Liaquat National Hospital and Medical College from November 2020 until December 2020. The undergraduate medical students (n=303) participated in the study. The questionnaires regarding barriers and motivators of social distancing were uploaded via Google forms to be filled by the participants. Chi squared test was applied for analysis among the variables and p value ≤0.05 was taken statistically significant. Results: The study showed social distancing motivators which included, social responsibility 174(57.5%), protecting sense for others in order to save them from getting sick 115(38%), and personal protection 126(41.5%). The current study reported that public lockdowns superimposed by the Government also accounted for social distancing 44(14.5%). Comparison of motivators of social distancing among gender was found to be statistically significant (p-value <0.05). However, insignificant comparison of barriers was found among genders (p=0.151). Conclusion:  Social responsibility factor was sufficiently same in both the genders (p=0.01). However, self- protection was the major motivator for practicing social distancing among female participants of the study when compared with males. Keywords: Social Distancing; Covid 19; Pandemic; Social Responsibility.